2006
DOI: 10.1590/s0103-84782006000600041
|View full text |Cite
|
Sign up to set email alerts
|

Efeito do tipo de ramo e do regime de luz fornecido à planta matriz no estabelecimento in vitro de araçazeiro cv. "Irapuã"

Abstract: Este trabalho objetivou avaliar o efeito do regime de luz submetido à planta matriz e do tipo de ramo utilizado no estabelecimento in vitro de araçá cultivar "Irapuã". O meio de cultura utilizado foi o MS acrescido de 5mM de BAP. Segmentos nodais retirados de ramos herbáceos e semilenhosos, contendo uma gema, de plantas mantidas no escuro durante 15 dias e de plantas mantidas sob luz, foram inoculados em tubo de ensaio contendo 10mL de meio. Após a inoculação, os explantes foram submetidos ao escuro sob temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
4

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 2 publications
1
2
0
4
Order By: Relevance
“…These authors had problems with bacterial contamination (average of 50%, with 95% for the control group) and fungal contamination (average of 13.34%, with 55% for the control group). Similar data was observed by Souza, Schuch, and Silva (2006) who, when testing the introduction of P. cattleianum cv. "Irapuã" using semi-lignified and herbaceous shoots, found that the average percentage of bacterial and fungal contaminations were 89.68% and 46.85%, respectively.…”
Section: In Vitro Establishment Of Red Araçá Seedlingssupporting
confidence: 84%
“…These authors had problems with bacterial contamination (average of 50%, with 95% for the control group) and fungal contamination (average of 13.34%, with 55% for the control group). Similar data was observed by Souza, Schuch, and Silva (2006) who, when testing the introduction of P. cattleianum cv. "Irapuã" using semi-lignified and herbaceous shoots, found that the average percentage of bacterial and fungal contaminations were 89.68% and 46.85%, respectively.…”
Section: In Vitro Establishment Of Red Araçá Seedlingssupporting
confidence: 84%
“…A utilização de técnicas de cultura de tecidos com o objetivo de melhorar a rentabilidade das culturas tem-se apresentado como instrumento importante que pode ser explorado pelos pesquisadores, produzindo plantas com elevada qualidade sanitária (Souza et al, 2006).…”
Section: Introductionunclassified
“…In evaluating the effect of a light regime on the mother plant and the branch type used for the in vitro establishment of araça (Psidium spp. ), [13] observed lower rates of contamination when using nodal segment explants of herbaceous branches, and obtained the highest survival rates when the mother plants were kept in darkness. These results are likely due to the reduced exposure of younger branches to contamination in the environment from which the explants were harvested.…”
Section: In Vitro Establishment and Micropropagationmentioning
confidence: 89%